Effectiveness of herbs containing Curcuma xanthorrhiza, Elephantopus scaber L and Amaranthus tricolor L in iron deficiency anemia patients - ULFA FITRIANI; zuraida zulkarnain; Fajar Novianto; Enggar Wijayanti; Agus Triyono (Biodiversitas Journal of Biological Diversity, 2020)
Objective: this study aimed to evaluate the effectiveness of herbs containing Curcuma xanthorrhiza, Elephantopus scaber L and Amaranthus tricolor L compared with iron supplement in Iron Deficiency Anemia (IDA) subjects. Materials and Methods: a total of 128 subjects with IDA were recruited and randomly assigned to one of the two groups: Anemia herbs (AH) (n=64) and Iron supplement (IS) (n=64). The AH group received herbs containing Curcuma xanthorrhiza, Elephantopus scaber L and Amaranthus tricolor L two times daily and the IS group received Hufabion capsul for 4 weeks. Outcome measures were assesed 4 weeks after intervention. The outcomes of this study were hemoglobin (Hb), mean corpuscular volume (MCV), serum iron (SI), total iron banding capacity (TIBC) and quality of life (QOL) by using short form-36 (SF-36). Ethical Committee of NIHRD approval was obtained for this study. Results: A significant QOL effect in score of SF-36 of AH group was found after 4 weeks intervention (p<0,05). In contrast, no significant effect were found for the value of Hb, MCV , SI and TIBC (p>0,05) in the AH group. In the IS group, there were significant differences for value of Hb, MCV, SI, TIBC and SF-36 scores (p=0,000). Significant group effects were found for the value of Hb, MCV, SI and TIBC when comparing the IS group to AH group. There were also no significant differences between groups for QOL scores after 4 weeks intervention. Conclusion: Herbs containing Curcuma xanthorrhiza, Elephantopus scaber L and Amaranthus tricolor L proved to be an effective complementary therapy by improve QOL in the IDA patients.